Formulation and Evaluation of Sun Block Lotion Made from Virgin Coconut Oil (VCO) with the addition of the Extract of Telang Flower (Clitoria ternatea, L) and Pandan Leaves (Pandanumusa paradisiaca, L) - Ritonga, Nia Boru; Rini, Rini; Anggraini, Tuty (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2020)
Telang flowers (Clitoria ternatea, L) and pandan leaves (Pandanus paradisiaca) are plants that contain phytochemical components that are able to block sunlight from exposing the skin. While Virgina Coconut Oil (VCO) is able to moisturize and soften the skin. This study aims to determine the best formulation in protecting sunlight in application to the skin, as well as knowing the physical and chemical characteristics of skin lotion. This research uses an exploratory method with 2 treatments and 3 replications. The treatment is the addition of telang flower extract and pandan leaf extract to the VCO skin lotion. Evaluation is carried out on the physical and chemical properties and the level of panelist preference. The results showed different results from the two formulations, the highest protection value to the sun was the addition of telang flower extracts expressed by SPF 20.64, the antioxidant activity of 81.66%, pH of 6, 0.012% free fatty acids, a specific gravity of 0.94, 34880 cP viscosity, 65.25% stability, 6.0 cm spreadability, total plate count of 1.3 x 10-10 cfu / ml.